Analisis Hasil Belajar Pengetahuan Siswa Menggunakan Metode Cooperative Script pada Materi Sepak Bola Kelas X SMAN 1 Rengasdengklok - Rimanto Rimanto; Nana Suryana N; Akhmad Dimyati (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to analyze the learning outcomes of students' knowledge by using the cooperative script method in the learning process of soccer material, this study uses descriptive quantitative methods, with data collection techniques using questionnaires, in the form of multiple choice questions on the research subject, namely in class X students, at SMAN 1 Rengasdengklok, with the results of research that the use of the cooperative script method for students is very necessary in the process of teaching and learning activities, the cooperative script method must be taught by the physical education teacher to two students in one group, and students explain the material they have summarized to their students. group of friends in turn. In this study, researchers can give advice to students to be able to learn and understand the material being taught so that the method can be carried out well in learning and following the learning process carefully and still looks a bit confused in following the soccer learning process so that the material that has been conveyed understandable and can be in the maximum value of the lesson.